Comparison between Two Low Doses of Amitriptyline in the Management of Chronic Neck Pain: A Randomized, Double-Blind, Comparative Study - Atef Mohamed Sayed Mahmoud; Safaa Gaber Ragab; Maged Labib Boules; Joseph Makram Botros (Pain Research and Management)
Chronic neck pain (CNP) is a major concern for pain therapists. Many drugs including antidepressants such as amitriptyline have been used in the management of CNP. This study compared the efficacy and safety of 2 different doses of amitriptyline (5 mg and 10 mg at bedtime) in patients with CNP. A total of 80 patients of both sexes with idiopathic CNP, ranging in age from 18 to 75 years, were divided into 2 groups that received 5 or 10 mg oral amitriptyline at bedtime for 120 days. The primary outcome measure was neck pain disability index (NPDI). Neck pain intensity, Athens Insomnia Scale score, Hospital Anxiety and Depression Scale (HADS), side effects of the drug, and patient satisfaction were secondary outcome measures. NPDI decreased by 71.9% ± 13.4% in the 10 mg group compared to 47.3% ± 17.3% in the 5 mg group, representing a statistically significant difference (95% confidence interval: 27.3–12.6). Additionally, the 10 mg group showed greater mean reductions in pain score and HADS scores (both the anxiety and depression subscales), as well as improvement in sleep disturbance compared to the 5 mg group. A higher dose (10 mg) of amitriptyline at bedtime significantly reduced neck pain intensity, sleep disturbance, and anxiety and depression compared to a lower dose (5 mg) in patients with idiopathic and nontraumatic CNP after 120 days of treatment, with no significant difference between groups in the rate of side effects.